Centering Reciprocity and Accountability in Community-Based Research: How Meaningful Relationships with a Community Advisory Group Impacted Survey Development - Godderis, Rebecca; Root, Jennifer (Engaged Scholar Journal, 2023)
Community advisory boards (CAB) or groups (CAG) are frequently included in qualitative community-based research (CBR), particularly in the early phases of assessing need, impact, and design of a research project. Projects with emancipatory, liberatory, or decolonial emphases include CAGs in the spirit of inclusivity, representation, transformation, truth-telling, and participation, but the methodological value and impact of such groups often remains under-explored in reports about the research. It is also relatively uncommon to use CAGs in quantitative research. In our survey research about post-secondary instructors’ experiences of receiving student disclosures of gender-based violence, we used a time-limited, task-specific CAG to assist with survey development. In this report from the field, we discuss our approach to the inclusion of a CAG in our research, which emphasized reciprocity and accountability to community, and we explore how the use of a CAG directly impacted and strengthened the quantitative study.